Abundance and distribution of microplastics in tropical estuarine mangrove areas around Penang, Malaysia - Tan, Evonne; Mohd Zanuri, Norlaila Binti (Frontiers in Marine Science, 2023)
Introduction This study reports the abundance and distribution of microplastics in tropical estuarine mangrove areas in Penang, Malaysia. Methods Samples were collected by using a neuston net and Ponar grab at four study sites (Seberang Perai, Kuala Muda, Penaga and Balik Pulau). Results and Discussion A total of 8775 pieces were collected from the four sites, with abundance in coastal surface water, coastal bottom sediment, and estuarine sediment ranging between 201 ± 21.214 - 1407 ± 124.265 pcs/L, 255 ± 22.368 - 350 ± 25.892 pcs/kg, and 430 ± 7.234 - 4000 ± 29.174 pcs/kg respectively. Seberang Perai was found with the highest microplastics abundance in all compartments while fragment is the dominant morphology throughout all study sites. Stereomicroscopic analysis showed that microplastics are of numerous colours and irregular in shape while Field Emission Scanning Electron Microscope (FESEM) observed severe surficial weathering. Polyethylene is the most common identified polymer type via Fourier Transform Infrared Spectroscopy (FTIR) analysis and inorganic chemical compounds such as dimethylmercury were detected which pose a threat to organisms and the environment. The overall outcome suggests that human activities play a significant role in microplastic input into the estuarine environment and that the dominant polymer type in respective study site are closely related to the nature of human activities. This baseline study presents fundamental knowledge on microplastic pollution in the estuarine environment of Penang and encourages similar research to be conducted in the future for pollution control and management.